Kepemimpinan Pendidikan Islam dalam Pemikiran Al-Ghazali - Moh Takwil (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
Whether or not Islamic education is highly dependent on the quality of leadership that is in it, an Islamic education leader must be able to direct his lead to achieve educational goals. In this journal discusses Al-Ghazali's thoughts about ideal leadership in Islamic education. This study uses literature review through primary sources from Al-Ghazali's thought books and secondary from various sources, then analyzed and criticized using content analysis. The research results obtained are that in substance the leadership must always aim to achieve the pleasure of Allah Almighty. Al-Ghazali always puts on all activities aimed at achieving the pleasure of Allah Almighty. There are four basic components of personal leaders in the world of Islamic education. First he must have managerial skills that are able to make planning, organizing, implementing and evaluating. Second, he must have a trustful and responsible nature. Third, he must be a role model, which is a good example so that his leadership feels comfortable carrying out his orders. The fourth is always in running the leadership bound by syara law.